Tes Diagnostik Miskonsepsi Peserta Didik pada Materi Gaya Kelas IV Sekolah Dasar - Tsania, Aulia; Kurniawati, Wahyu (Universitas Muhammadiyah Magelang, 2024)
Science in general teaches to develop reasoning skills and be able for understand concepts, but in reality science learning there are still students who experience misconceptions. The purpose of the study is to determine the magnitude of misconceptions in 4th-grade students of SD Negeri Ngrukeman and to find out the causes of misconceptions, so that they can determine the right solution to the problem. This research uses quantitative descriptive research. The data collection technique used diagnostic tests and the subjects in this study were 4th-grade students of SD Negeri Ngrukeman. Based on the results of the diagnostic test, it is known that the percentage of students' misconceptions on the topic